Education, technology and high-quality economic development - Meiwen, Su; Ming, Ji; Mengyu, Li (International review of financial analysis, 2025)
The drivers of high-quality economic development in emerging economies remain a subject of intense debate. Although education and technology are recognized as crucial factors, their interplay, synergistic effects, and relative significance in the context of China's economic transformation are not yet fully understood. This study addresses this gap by examining the impacts of education and technology investments on high-quality economic development across Chinese provinces. Using panel data from 30 provinces over 2007–2022 as well as fixed effects models, mediation analysis, and interaction terms, this study determines the direct, indirect, and synergistic effects of these investments. Results reveal that education and technology positively influence high-quality development, and technology has a more pronounced direct effect. Human capital and information technology levels partially mediate these relationships, highlighting the complex pathways through which investments can translate into economic outcomes. Notably, we uncover a significant synergistic effect in which the impact of education (technology) investment is enhanced by higher levels of technology (education) investment. Furthermore, we find substantial regional heterogeneity, with technology investments yielding higher returns in less developed regions. These findings contribute to a more nuanced understanding of the drivers of high-quality economic development, offering insights for policymakers to optimize the balance and interaction between education and technology investments in diverse economic contexts. •Education and technology investments show positive effects on economic development, with technology having stronger immediate impact.•Human capital and informatization levels partially mediate investment impacts, revealing complex development pathways.•Technology investments yield higher returns in less developed regions, suggesting targeted policy opportunities.•Education-technology synergies enhance development outcomes, indicating benefits of coordinated investment strategies.•Regional variations in investment effectiveness highlight need for context-specific development policies.